2005
DOI: 10.1037/0735-7044.119.1.202
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Central Nucleus Function Is Necessary for Learning, but Not Expression, of Conditioned Auditory Orienting.

Abstract: When exposed to pairings of a visual stimulus with food delivery, rats normally acquire both conditioned orienting responses directed toward the visual stimulus and conditioned food-related responses. Consistent with the results of previous lesion studies, reversible inactivation of amygdala central nucleus function before each conditioning session prevented the acquisition of conditioned orienting responses, whereas food-related behaviors were acquired normally. By contrast, neither inactivation nor neurotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 54 publications
3
34
2
Order By: Relevance
“…Based on previous findings in our laboratory (24), we expected the dorsal amygdala and anterior hippocampus to be activated both in anticipation of and response to aversive pictures, consistent with the idea that there is one system that governs both processes (26,43). Work highlighting the role of the amygdala, especially the dorsally located central nucleus of the amygdala (CeA), in modulating attention and perception of motivationally salient events (2,3,7,(44)(45)(46)(47)(48)(49)(50)(51)(52) leads to the prediction that dorsal amygdala activation in anticipation of and response to aversive pictures may show a particularly strong association with encoding and immediate recognition of those pictures. Research establishing the hippocampus as a primary neural substrate for episodic memory (53)(54)(55)(56)(57) suggests that anterior hippocampus activation in this study would predict both immediate and delayed recognition.…”
mentioning
confidence: 76%
“…Based on previous findings in our laboratory (24), we expected the dorsal amygdala and anterior hippocampus to be activated both in anticipation of and response to aversive pictures, consistent with the idea that there is one system that governs both processes (26,43). Work highlighting the role of the amygdala, especially the dorsally located central nucleus of the amygdala (CeA), in modulating attention and perception of motivationally salient events (2,3,7,(44)(45)(46)(47)(48)(49)(50)(51)(52) leads to the prediction that dorsal amygdala activation in anticipation of and response to aversive pictures may show a particularly strong association with encoding and immediate recognition of those pictures. Research establishing the hippocampus as a primary neural substrate for episodic memory (53)(54)(55)(56)(57) suggests that anterior hippocampus activation in this study would predict both immediate and delayed recognition.…”
mentioning
confidence: 76%
“…In the same study, the authors showed that the medial CeA cells retrogradely labeled from the SNc expressed an immediate-early gene, FOS, after conditioned orienting responses, demonstrating the direct involvement of the CeA to SNc projection in conditioned orienting. Furthermore, a series of studies demonstrated time dependencies such as those observed by Holland and Gallagher (2006): CeA function was critical only at the time of acquisition (McDannald et al, 2004;Groshek et al, 2005), and function of another brain region, the dorsal lateral striatum, was critical only at the time of expression of that learned response (Han et al, 1997). Most important, SNc function was critical to both the acquisition and expression of that behavior (El Almamy and Holland, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that, unlike instrumental responses on discrimination tasks, the expression of conditioned cardiovascular responses in Pavlovian tasks depends on an intact amygdala (33). Moreover, the acquisition of various conditioned behaviors including CSelicited approach (34) and orienting responses also depend on an intact amygdala (35,36), despite their expression being amygdala-independent (M.S.M., K.B., Y. Mikheenko, and A.C.R., unpublished results and refs. [35][36][37].…”
Section: Discussionmentioning
confidence: 99%